An Investigation of the Practice of Effective Teaching Strategies in Three Islamic Senior High Schools in South Jakarta - Lia Aida (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
Some research has argued that effective teachers significantly influence students’ performance. However, becoming effective teachers are not easy because they have to apply some strategies of effective teaching. For that reason, this paper intends to investigate whether teachers from three Islamic Senior High Schools in South Jakarta practice effective teaching strategies. These schools have been considered good due to the high mean score of English subject in Ujian Nasional. The framework of effective teaching follows the model developed by Creemers and Kyriakides, which relate teacher behavior in the classroom and student achievement . The framework consists of orientation, structuring, questioning, teaching modeling, applications, teacher role in making classroom a learning environment, management of time, and classroom assessment.